Are TQM practices supporting customer satisfaction and service quality? - Ooi, Keng Boon; Lin, Binshan; Tan, Boon In; Chong, Alain Yee Loong (Emerald, 2011)
Purpose – The purpose of this paper is to examine the relationship between total quality management (TQM) practices and customer satisfaction and also to investigate the association between TQM practices and service quality within the context of Malaysia’s small service organizations. Design/methodology/approach – The paper uses data from the perceptions of sales and marketing managers in 108 small service organizations in Malaysia. Data were analyzed by employing correlation and multiple regression analysis to test the relationship between TQM practices, customer satisfaction and service quality. Findings – The results showed that TQM practices are significantly and positively linked to customer satisfaction and service quality of the small service business firms. It was further confirmed that the dimensions of customer focus and information and analysis were strongly linked to customer satisfaction and service quality. Practical implications – The results of this paper can be used by marketing/sales managers to prioritize the adoption of the dimensions for TQM practices. For instance, those dimensions that are found to have positive influence on customer satisfaction and service quality can be recommended to marketing/sales managers so that they can allocate resources to improve these practices to achieve higher customer satisfaction and quality of service. Originality/value – This paper identifies two dimensions of TQM namely, customer focus and information and analysis that can influence customer satisfaction and service quality in Malaysia’s small service business firms.